KAJIAN DRUG RELATED PROBLEMS (DRPs) PADA PASIEN INTENSIVE CARE UNIT (ICU) DI RUMAH SAKIT ISLAM “X” - Ningrum, Dwi Monika; Ulandari, Atri Sri; Setia Permana, Denih Agus (Jurnal Kesehatan Qamarul Huda, 2023)
A hospital's designated location where patients with injuries get specialist nursing and medical care is called an intensive care unit, or ICU. Given that the intensive care unit (ICU) is a treatment location that requires a significant investment in both personnel (specialists) and technology, patients treated there often have acute conditions that are believed to be reversible (recoverable). Drug Related Problems (DPRs) are unintended side effects of medication treatment that patients may face and which may compromise their chances of making a full recovery. Regarding DRPs, errors in dosage and medication interactions may occur during treatment in the intensive care unit, or the dosage may be administered incorrectly. This investigation is a part of a descriptive research that used a retrospective data gathering strategy from 30 medical records of patients who were hospitalised to the intensive care unit between July and September of 2022. Next, a literature research analysis was used to examine the presence of DRPs using BNF 73 (2017), www.drugs.com, and ESC (2016). The category of medication dose and the possibility of drug interactions were taken into consideration while examining the DRPs in this investigation. In the dosage category, the study's findings were gathered from 30 active patients; among them, 28 patients (93.3%) had the appropriate dose chosen when it came to ICU patients, while 2 patients (6.7%) had overdosed. In the category of Potential Drug Interactions obtained from 30 ICU patients, major potential drug interactions were found in 14 patients (46.7%). Of the patients, 27 individuals had a moderate prevalence of possible medication interactions (90%). Finally, 15 individuals (50%), encountered the occurrence of possible mild medication interactions.